Pemberdayaan Masyarakat Melalui Pemanfaatan Eco Enzym Sebagai Substitusi Cairan Pembersih Domestik di Banjar Panti Gede, Pemecutan Kaja - Made Sattyatma Naryndra Pradnyana; Anak Agung Adi Wiryya Putra; Made Chandri Maharani Sukma Dewi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The main objective of this community service is to address the high volume of domestic organic waste through the socialization and assistance of Eco Enzyme production as a substitute for household cleaning fluids in Banjar Panti Gede, Pemecutan Kaja. The significance of this program lies in its potential to mitigate environmental pollution caused by synthetic chemical cleaning residues while providing an alternative for family economic savings. This study employed a participatory descriptive qualitative design involving 75 PKK members and the Kelian Adat. Data were collected through questionnaires (pre-test and post-test) and structured observations using rubrics, which were then analyzed using qualitative descriptive statistics. Key findings indicate a measurable increase in residents' cognitive understanding of chemical residue hazards (from 32% to 88%) and mastery of the 1:3:10 formulation ratio (from 15% to 96%). Psychomotor evaluation proved that 92% of participants successfully practiced producing Eco Enzyme independently. The challenge of fermentation duration was effectively addressed using prototype samples and digital group mentoring. The implications confirm that a cultural approach involving traditional leaders combined with digital monitoring effectively builds community independence in maintaining the ecosystem. It is recommended that this hybrid empowerment model be adopted in village-level waste management policies and replicated in other local communities to expand the impact of a green lifestyle.